Master’s exam for A.V. Chayanov - Savinova Tatyana A (Крестьяноведение)
This is the letter from the Professor of the Moscow Agricultural Institute V.Ya. Zheleznov to A. F. Fortunatov with requirements for the program of the Master’s exam in Political Economy for the graduate A. V. Chayanov.